THE PART DIRECT ADDRESS AND PRONOUNS PLAY IN CHANGING VISITOR PERCEPTIONS IN TURKISH TOURISM ADVERTISING (TAMADDUN NURI JURNALI, 2025)
This study explores the pragmatic functions of direct address and personal pronouns in Turkish tourism advertising, focusing on how linguistic strategies foster emotional engagement, cultural identification, and enhance the perceived hospitality of Türkiye as a travel destination.